OP0132 Low-dose INTERLEUKIN-2 selectively restore regulatory T cell numbers in patients with behcet's disease. (15th June 2017) - Fu, X; Li, J; Li, X; Luo, J; Gao, C; Chen, Q
Abstract : Background: The lack of CD4 + CD25 + Foxp3 + T regulatory cell (Treg) has been associated with human systemic autoimmune diseases, such as Behcet's disease (BD). IL-2, an essential growth and survival factor for Treg cells.However, the significance of Treg cells in the pathogenesis and the effect of low dose of IL-2 on BD are remain to investigate. Objectives: The lack of CD4 + CD25 + Foxp3 + T regulatory cell (Treg) has been associated with human systemic autoimmune diseases, such as Behcet's disease (BD). IL-2, an essential growth and survival factor for Treg cells.However, the significance of Treg cells in the pathogenesis and the effect of low dose of IL-2 on BD are remain to investigate. Methods: Eighty patients with BD and seventy healthy donors were enrolled. CD4 + T cell subsets in peripheral blood mononuclear cells from these people were measured by multicolour flow cytometry. Twenty-six patients were treated daily with subcutaneous injections of 0.5 million IU of human IL-2 for five consecutive days, CD4 + T cell subsets were analysed before and after treatment by flow cytometry. Results: Compared to health control, the absolute counts of circulating Treg cells were significantanty decreased in patients with BD (median:29.93 cell/uL VS median:33.16 cell/uL; p=0.039) and it is negative correlation with disease activity. While the ratios of Th17/Treg in patients with BD (median:0.29;n=80, p=0.034) were significantly higher than those of health control (median:0.2;n=70).No diffrernce in the absolute counts of circulating Th17 cells (CD4 + IL-17 + ) between patients with BD and health control. Treatment of patients with BD with a low-dose of IL-2 regimen selectively increased the absolute counts of Treg cells, from a median of 18.97cell/uL to 74.68 cell/uL (at 5 days) (p=0.000). No significant difference was observed in the absolute counts of circulating Th17, Th1 and Th2 cells after IL-2 treatment. Conclusions: Th17/Treg cells may play a role in the pathogenesis of Patients with BD, low-dose of IL-2 proposes a selective biological treatment strategy by restoring immune tolerance. Disclosure of Interest: None declared